Meta-analysis of molecular imaging of translocator protein in major depression - Eggerstorfer, Benjamin; Kim, Jong-Hoon; Cumming, Paul; Lanzenberger, Rupert; Gryglewski, Gregor (Frontiers in Molecular Neuroscience, 2022)
Molecular neuroimaging studies provide mounting evidence that neuroinflammation plays a contributory role in the pathogenesis of major depressive disorder (MDD). This has been the focus of several positron emission tomography (PET) studies of 17-kDa translocator protein (TSPO), which is expressed by microglia and serves as a marker of neuroinflammation. Consequently, in this meta-analysis we aimed to compile and analyze all available molecular imaging studies comparing cerebral TSPO binding in MDD patients with healthy controls. Our systematic literature search yielded eight PET studies encompassing 238 MDD patients and 164 healthy subjects. The meta-analysis revealed significantly increased TSPO binding in at least five brain regions (anterior cingulate cortex: Hedges’ g = 0.6, 95%CI: 0.36,0.84; prefrontal cortex: g = 0.36, 95%CI: 0.14,0.59; insula: g = 0.43, 95%CI: 0.17,0.69; hippocampus: g = 0.54, 95%CI: 0.26,0.81; temporal cortex: g = 0.39, 95%CI: -0.04,0.81). The variance of effect sizes in the temporal cortex might reflect group-differences in body mass index (BMI), but exploratory analyses failed to find any relationship between the elevated TSPO availability in the other four significant brain regions and depression severity, age, BMI, radioligand and binding endpoint used, or treatment status at time of scanning. Collectively, this meta-analysis indicates a widespread 18% increase of TSPO availability in the brain of MDD patients, with effect sizes comparable to those in earlier molecular imaging studies of serotonin transporter availability and monoamine oxidase A binding. This result is consistent with increased microglial activation being a feature of MDD.